Adverse psychosocial work factors, blood pressure and hypertension incidence: repeated exposure in a 5-year prospective cohort study. Issue 4 (3rd November 2015) - Trudel, Xavier; Brisson, Chantal; Milot, Alain; Masse, Benoit; Vézina, Michel
Abstract : Background: Two main theoretical models have been used to assess the impact of psychosocial work factors on blood pressure (BP): the demand–control (DC) model and the effort–reward imbalance (ERI) model. Previous studies have mostly used a single time point exposure to examine this association. Objective: To examine the effect of repeated job strain and ERI exposure on (1) ambulatory BP (ABP) evolution over 5 years and (2) hypertension incidence over 5 years. Method: The design is a prospective cohort study. The study population was composed of 1394 white-collar workers (568 men and 826 women). They were assessed three times during a 5-year period (years 1, 3 and 5). At each time, psychosocial work factors were measured using validated scales and ABP was measured every 15 min during a working day. Results: Men who were chronically exposed over 5 years to an active job had a higher cumulative incidence of hypertension (RR=2.05, 95% CI 1.36 to 3.09), compared with never-exposed men. In women, ERI exposure onset was associated with higher increases in systolic ABP (+2.5 mm Hg). No association was found between chronic high-strain exposure and ABP. Conclusions: Chronic exposure to active jobs in men led to a higher risk of hypertension and ERI exposure onset in women led to increases in systolic ABP. Results from the present study highlight the need to consider chronic exposure in order to fully capture the deleterious effect of adverse psychosocial work stressors on cardiovascular health.